The SAMI Pilot Survey: the kinematic morphology-density relation in Abell 85, Abell 168 and Abell 2399 - Fogarty, L; Scott, N; Owers, MS; Brough, S; Croom, S; Pracy, M; Houghton, R; Bland-Hawthorn, J; Colless, M; Davies, R; Jones, D; Allen, J; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We examine the kinematic morphology of early-type galaxies (ETGs) in three galaxy clusters Abell 85, 168 and 2399. Using data from the Sydney-AAOMulti-object Integral field spectrograph we measure spatially resolved kinematics for 79 ETGs in these clusters. We calculate λR, a proxy for the projected specific stellar angular momentum, for each galaxy and classify the 79 ETGs in our samples as fast or slow rotators. We calculate the fraction of slow rotators in the ETG populations (fSR) of the clusters to be 0.21 ± 0.08, 0.08 ± 0.08 and 0.12 ± 0.06 for Abell 85, 168 and 2399, respectively, with an overall fraction of 0.15 ± 0.04. These numbers are broadly consistent with the values found in the literature, confirming recent work asserting that the fraction of slow rotators in the ETG population is constant across many orders of magnitude in global environment. We examine the distribution of kinematic classes in each cluster as a function of environment using the projected density of galaxies: the kinematic morphology-density relation.We find that in Abell 85 fSR increases in higher density regions but in Abell 168 and 2399 this trend is not seen. We examine the differences between the individual clusters to explain this. In addition, we find slow rotators on the outskirts of two of the clusters studied, Abell 85 and 2399. These galaxies reside in intermediate to low density regions and have clearly not formed at the centre of a cluster environment. We hypothesize that they formed at the centres of groups and are falling into the clusters for the first time. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.